Crescentic glomerulonephritis: A clinical and histomorphological analysis of 46 cases - Ruchika Gupta; Lavleen Singh; Alok Sharma; Arvind Bagga; Sanjay K Agarwal; Amit K Dinda (Wolters Kluwer Medknow Publications, 2011)
Background: Crescentic glomerulonephritis (CrGN), defined as crescents involving more than 50% of the glomeruli, includes pauci-immune, immune complex-mediated and anti-glomerular basement membrane disease. Objectives: The present study was aimed at evaluating the various clinical, biochemical and histological parameters in CrGN with respect to these categories and clinical outcome. Materials and Methods: Renal biopsies diagnosed as CrGN between Jan 2008 and Feb 2010 were included. Clinical and laboratory parameters were retrieved along with the therapeutic approach and clinical outcome, wherever available. Renal biopsy slides were evaluated for various glomerular, tubulo-interstitial and arteriolar features. Appropriate statistical tests were applied for significance. Results: A total of 46 cases of CrGN were included; majority (71.7%) of cases were pauci-immune (PI) while 28.3% were immune complex-mediated (IC). Among clinical features, gender ratio was significantly different between PI and IC groups (P = 0.006). The various histological parameters, including proportion of cellular crescents, tuft necrosis and Bowman's capsule rupture, were similar in both the groups. Four unusual associations, including idiopathic membranoproliferative glomerulonephritis (MPGN), multibacillary leprosy, acute lymphoblastic leukemia and C1q nephropathy were detected. Adequate follow-up information was available in 21 (46%) of the patients. Of these, 11 (52.4%) were dialysis-dependent at the last follow-up. Adult patients required renal replacement therapy more frequently than pediatric cases (P = 0.05). Presence of arteriolar fibrinoid necrosis also showed association with poor clinical outcome (P = 0.05). Conclusions: Crescentic glomerulonephritis remains one of the main causes of acute renal failure with histological diagnosis. Immunohistologic examination is essential for accurate classification into one of the three categories. This condition should be considered in rare causal associations like leprosy or MPGN with renal failure, to allow for timely performed renal biopsy and appropriate aggressive therapy.